1988
DOI: 10.1002/cne.902670207
|View full text |Cite
|
Sign up to set email alerts
|

Medullary sources of projections to the kinesthetic thalamus in raccoons: External and basal cuneate nuclei and cell groups x and z

Abstract: In raccoons and other mammals, a pathway for kinesthetic sensation (from muscles, fascia, tendons, and joints) reaches the anterodorsal cap of the ventrobasal thalamus and the anteriormost part of the somatic sensory cerebral cortex. To find the medullary component of this kinesthetic pathway in raccoons, small injections of horseradish peroxidase were made in the thalamus under guidance of simultaneous electrophysiological recording from kinesthetic projections. As determined by retrograde labeling following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Like the somatotopic arrangement of the CuM clusters (see DCN somatotopy, cuneate nuclei section), the ECu‐thalamic projections are present in rats, raccoons, and monkeys, but not in cats. This further supports the notion that the DCN‐complex is functionally organized for dexterous limb and digit control in these animals, as noted by Ostapoff et al (1988). Raccoons are more phylogenetically similar to cats than to rats or monkeys, yet cats lack ECu‐thalamic connections, and have different somatotopic DCN organization, which may be related to their lack of forepaw dexterity.…”
Section: Dcn Projection Targets and Connectionssupporting
confidence: 89%
See 1 more Smart Citation
“…Like the somatotopic arrangement of the CuM clusters (see DCN somatotopy, cuneate nuclei section), the ECu‐thalamic projections are present in rats, raccoons, and monkeys, but not in cats. This further supports the notion that the DCN‐complex is functionally organized for dexterous limb and digit control in these animals, as noted by Ostapoff et al (1988). Raccoons are more phylogenetically similar to cats than to rats or monkeys, yet cats lack ECu‐thalamic connections, and have different somatotopic DCN organization, which may be related to their lack of forepaw dexterity.…”
Section: Dcn Projection Targets and Connectionssupporting
confidence: 89%
“…Nucleus X comprises small to medium-sized loosely scattered cells found rostral to the ECu (Figure 1a, insert; in rats (Mantle-St. John & Tracey, 1987), cats ( Johansson & Silfvenius, 1977b), raccoons , and nonhuman primates (Albright & Friedenbach, 1982;Pearson & Garfunkel, 1983), but is rarely identified in humans (Kaas, 2004), likely because it is difficult to identify histologically. Nucleus X receives secondary afferents responsive to activation of ipsilateral hindlimb muscles, joints, and skin, which are primarily collaterals of dsc neurons from the nucleus dorsalis (Johansson & Silfvenius, 1977b;Landgren & Silfvenius, 1971;Low et al, 1986;Mantle-St. John & Tracey, 1987;Ostapoff, Johnson, & Albright, 1988). In raccoons, X also receives some input from forelimb muscle, tendon, and joint afferents that ascend in the dLF , but it is unclear if these are primary or secondary afferents, or whether the same inputs are found in other species.…”
Section: Nuclei X and Zmentioning
confidence: 99%
“…Differential studies of retrograde cell labeling, following HRP injections into the ventral posterior lateral thalamic nucleus, demonstrated that many cells in the medial basal pericuneate zone (PCu) that convey tactile information also project to the thalamus through the medial lemniscus with gracile and cuneate axons. However, Ostapoff et al (1988) have concluded that what might be the homologs of the PCu cells in the racoon relay deep subcutaneous kinesthetic sensations ending chiefly in the ventral intermediate (Vim)like shell region rostral to the tactile thalamic nucleus. They also confirmed that the caudally situated cells of subgroup X project to the cerebellum, but cells they identified as rostrally situated subgroup X, like nucleus Z, also project to the thalamic shell region.…”
Section: Afferent Connections Of the Pericuneate And Peritrigeminal Nmentioning
confidence: 99%
“…Nucleus X comprises small to medium-sized loosely scattered cells found rostral to the ECu (Figure 1A, insert) (A. in rats (Mantle-St. John & Tracey, 1987), cats (H. Johansson & Silfvenius, 1977b), raccoons , and nonhuman primates (Albright & Friedenbach, 1982;Pearson & Garfunkel, 1983), but is rarely identified in humans (Kaas, 2004), likely because it is difficult to identify histologically. Nucleus X receives secondary afferents responsive to activation of ipsilateral hindlimb muscles, joints, and skin, which are primarily collaterals of DSCT neurons from the nucleus dorsalis (H. Johansson & Silfvenius, 1977b;Landgren & Silfvenius, 1971;Low et al, 1986;Mantle-St. John & Tracey, 1987;Ostapoff, Johnson, & Albright, 1988). In raccoons, X also receives some input from forelimb muscle, tendon, and joint afferents that ascend in the dLF , but it is unclear if these are primary or secondary afferents, or whether the same inputs are found in other species.…”
Section: Nuclei X and Zmentioning
confidence: 99%